The Influence of Financial Report Transparency and Zakat Fund Management during the Pandemic on the Level of Muzakki Trust - Siahaan, Ummi Salamah Afnita Sari; Samri Juliati Nasution, Yenni; Syafina, Laylan (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
In the era of increasingly advanced globalization, transparency of financial reports and management of zakat funds has become imperative to describe its use and benefits for people in need. This research aims to examine the influence of financial report transparency on muzakki’s level of trust in BAZNAS Medan City. This research also explores the influence of Zakat Fund Management on muzakki’s Trust Level. Data was collected through a questionnaire survey distributed to a sample of 80 respondents. A quantitative approach was used, and multiple regression analysis was performed using STATA software. The results of the research show that transparency of financial reports does not significantly influence the trust level of muzakki in BAZNAS Medan City, while the management of zakat funds by Islamic principles has a greater impact on the level of trust of muzakki in BAZNAS Medan City, this can be through factors such as integrity, success in achieving social goals, and effective communication.